If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
66 = (6/5)*(x+3) // - (6/5)*(x+3)
66-((6/5)*(x+3)) = 0
(-6/5)*(x+3)+66 = 0
66-6/5*(x+3) = 0
66-6/5*(x+3) = 0
312/5-6/5*x = 0
312/5-6/5*x = 0
312/5-6/5*x = 0 // - 312/5
-6/5*x = -312/5 // : -6/5
x = -312/5/(-6/5)
x = 52
x = 52
| m+(13)=37 | | (4x^3)-(12x^2)+(2x)+(18)=0 | | -4(0)+2y=10 | | (n+8)(n-3)=-30 | | -4x+2(0)=10 | | .5x-3=-1 | | 16x^2-46x+15=0 | | x^2-324=2x | | 2(8x-5)=4 | | -18n=-180 | | 16/7x/2/35x | | 3y^2-14y-5=0 | | -6x^4+36x^3+30x^2= | | 2y=-3x | | 9+x/3=-10 | | v+25=77 | | (7/12)+(5/18) | | 6/102= | | x^2+y=5x-8 | | 102/6= | | 3x-11=-17 | | 3b^2-30b=6b-60 | | (a+2)/2=-1 | | 2x-4/6=6x+2/x-6 | | (-16/11)/(4/9) | | x^2+y+8=5x | | (-1/15)+(-14/15) | | 6x+30=25x-20 | | 2x^2-12x+36= | | d*d+18(d+4)=-9 | | s*s-3(s+2)=4 | | 0=-7.5(x^2-4x-320) |